Features of vertical stability of junior school children with visual impairments - Yurchenko A. A. (Kharkov National Pedagogical University, 2012)
The importance of vertical stability in the formation of the spatial organization of the body and correct posture for junior school children with visual impairments was determined. In a pilot study involved 23 children with low vision and 60 healthy children, aged 7-10 years old. To obtain the results was used the test of E.Y. Bondarevskogo. The features of orthograde posture of children with low vision and their healthy peers. Distinctive features in terms of retention of vertical posture and goniometric characteristics have been revealed. Found that junior school children with low vision by about 60-65% yield in the reported figures from their healthy peers. The visually impaired junior school children have significantly less ability to retain the static vertical posture than children with normal vision have been proved and verified.